Monetary and financial statistics: compilation guide - International Monetary Fund.; International Monetary Fund. (Washington, D.C. : The Fund, 2000)
The guide focuses on the cross-country harmonization of source data and methodology for the compilation and presentation of the statistics. It also describes the unified framework for countries' reporting of monetary data in the IMF. This is an accompaniment to the Monetary and Financial Statistics Manual. It is a significant component of the IMF work on enhacing the quality, availability, and analytical usefulness of financial sector data in both in-country and international context.
Includes bibliographical references and index.
oif 02/12/13
Loan
Keywords: Money -- Statistics -- Handbooks, manuals etc; Finance -- Statistics -- Handbooks, manuals etc; International Monetary Fund